2000
DOI: 10.1023/a:1008319114278
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians' knowledge and attitudes towards genetic testing for breast-ovarian cancer predisposition

Abstract: The majority of the primary care physicians in this study have a favourable attitude and are ready to play a prominent role in genetic counseling and testing for breast ovarian cancer predisposition. Defective knowledge scores, however, underline the need for targeted educational programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 24 publications
9
74
0
5
Order By: Relevance
“…This association between knowledge scores and gender was not found in other studies on genetics knowledge among physicians in the Netherlands (Baars MJH et al, unpublished data, 2005). 4,6 In general, no differences were found between students from different medical schools, except that students from one medical school (A) scored significantly lower, compared to those from two of the other six medical schools (E and G).…”
Section: Genetic Knowledge Among Medical Studentsmentioning
confidence: 87%
See 2 more Smart Citations
“…This association between knowledge scores and gender was not found in other studies on genetics knowledge among physicians in the Netherlands (Baars MJH et al, unpublished data, 2005). 4,6 In general, no differences were found between students from different medical schools, except that students from one medical school (A) scored significantly lower, compared to those from two of the other six medical schools (E and G).…”
Section: Genetic Knowledge Among Medical Studentsmentioning
confidence: 87%
“…[1][2][3][4]7 However, genetic knowledge and skills are relevant because the recent rapid developments in this field have given rise to increasing patient demands for management of the genetic aspects of their illnesses, requiring doctors to be increasingly more equipped to deal with these demands. 15 This situation could be improved by allocating more time to genetics in the curricula.…”
Section: Genetic Knowledge Among Medical Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low perceived clinical utility, as well as concerns about potential discrimination, have repeatedly been reported as primary barriers to uptake of both traditional genetic testing and newer applications [35][36][37][38][39] . Similarly, we found that uncertain clinical utility was among the top concerns of respondents for themselves and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, however, general practitioners (GPs) find this 'gatekeeper' role difficult, both in the UK (Fry et al, 1999;Bankhead et al, 2001;Rose et al, 2001;Walter et al, 2001;Elwyn et al, 2002;Campbell et al, 2003) and elsewhere (Escher and Sappino, 2000). The proportion of referrals to breast cancer family clinics that fall below the required risk threshold has been reported as almost 25% in one large UK-wide survey (Wonderling et al, 2001).…”
mentioning
confidence: 99%